Increasing Trend of Summer Monsoonal Rainfall Tied to the Extension of the South China Sea Summer Monsoon Duration - Lang Song; Peng Hu; Wen Chen; Ruowen Yang; Tianjiao Ma; Yuqiong Zheng (Atmospheric Science Letters)
ABSTRACT Previous studies on the South China Sea Summer Monsoon (SCSSM) mainly focused on a certain stage of its seasonal march. In this manuscript, we consider the monsoon onset and retreat as a whole and analyze the duration of the SCSSM and the monsoonal rainfall. We first verify the reasonableness of the SCSSM onset and retreat dates derived from the National Climate Center of China Meteorological Administration, and thus obtain the monsoon duration. Direct validation shows that longer SCSSM durations are associated with the anomalous westerly wind and warm–humid airmass, and vice versa, and thus the monsoon duration is trustworthy. The SCSSM duration shows remarkable low‐frequency variations after the mid‐2000s (increasing from 25.2 pentads to 28.5 pentads), which is mainly associated with the interdecadal delayed monsoon retreat. Corresponding to the extension of SCSSM duration by more than half a month, the monsoonal rainfall across the East Asia–western North Pacific also shows a significant increase. Compared to the traditional summertime rainfall over a fixed period (i.e., from May to September), our newly defined monsoonal rainfall (i.e., total rainfall within the monsoon duration) may be more physically meaningful and reflective of climatic changes.